2010
DOI: 10.4310/mrl.2010.v17.n3.a1
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of high index topologically minimal surfaces

Abstract: Abstract. The topological index of a surface was previously introduced by the first author as the topological analogue of the index of an unstable minimal surface. Here we show that surfaces of arbitrarily high topological index exist.Consider a compact, connected, two sided surface S properly embedded in a compact, orientable 3-manifold M . The disk complex Γ(S) is the simplicial complex defined as follows: Vertices of Γ(S) are isotopy classes of compressing disks for S. A collection of n such isotopy classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 3 publications
(3 reference statements)
0
32
0
Order By: Relevance
“…The proof of Theorem 1.5 is also used by Bachman in [1] to study stabilization of Heegaard splittings.…”
Section: Definition 13mentioning
confidence: 99%
See 1 more Smart Citation
“…The proof of Theorem 1.5 is also used by Bachman in [1] to study stabilization of Heegaard splittings.…”
Section: Definition 13mentioning
confidence: 99%
“…Y ) if, there is an essential curve in P t such that (1) bounds a compressing disk in X t (resp. Y t ), and (2) M 2 and bounds an embedded disk D in M 2 that is transverse to P t .…”
Section: Next We Show That There Is a Curvementioning
confidence: 99%
“…Recent work has shown that in some sense (low genus) Heegaard splittings of "generic" 3-manifolds are amalgamations (see eg Bachman [1], Bachman, Schleimer and Sedgwick [4], Lackenby [15], Li [16] and Souto [27]). Not every Heegaard splitting, however, is an amalgamation of Heegaard splittings along some essential surface.…”
Section: The Stabilization-amalgamation Problemmentioning
confidence: 99%
“…Definition 1.1. [4] F is critical if the compressing disks for F can be partitioned into two sets C 0 and C 1 , such that (1) for each i = 0, 1, there is at least one pair of disks…”
Section: Introductionmentioning
confidence: 99%
“…Critical surfaces, which are also defined by David Bachman [1] [4], can be regarded as topological index 2 minimal surfaces [4]. Definition 1.1.…”
Section: Introductionmentioning
confidence: 99%